Development of a core outcome set for third molar surgery - Carr, Richard William Fraser (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2024)
Introduction: Third molar surgery (TMS) is one of the most common operations in the world and a wealth of research is done in this field evaluating various interventions for the improvement of patient outcomes. In the age of evidence-based medicine, dependent on robust recommendations from thorough evidence synthesis, there is a need for standardised study design and reporting. Core outcome sets (COS) are an innovation in reporting that can address this and there is a need for a COS in third molar surgery since there is evidence of wide outcome heterogeneity currently. The current work forms the pre-consensus stages of a wider COS in this field (The CORE8 Study). Aim & Objectives: To investigate the current reporting of outcomes in trials in TMS as well as what outcomes are most important to patients by: 1) Assessing current outcome reporting through a scoping review, and 2) Identifying what outcomes are important to patients who are undergoing lower third molar surgery through qualitative focus groups. Methods: A scoping review (CORE8.1) was carried out, following the scoping review methodological framework from the Joanna Briggs Institute. CORE8.1 was reported in line with the ‘Preferred Reporting Items for Systematic Reviews and Meta-analyses’ scoping review extension. A qualitative study (CORE8.2) was conducted via online focus groups, utilising a topic guide designed following CORE8.1. Recruitment was purposive, from oral surgery clinics within Dublin Dental University Hospital. The focus group data were transcribed and analysed inductively using framework analysis. Reporting was in line with consolidated criteria for reporting qualitative studies. Results: CORE8.1 – The search strategy identified 5,613 unique references and 815 interventional studies were included in the full data extraction. The most common topic was analgesia. 82 outcomes were identified, summarised in four domains (physical, psychological, practical, quality of life) including six physical sub-domains (pain, swelling, function, healing, systemic response and complications). CORE8.2 collected a wealth of insights into outcomes of importance to patients across two focus groups, including 10 patients. Key findings across nine themes included the importance of physical symptoms like pain, practical challenges like diet and work, psychological issues like anxiety and quality of life issues including recovery and sleep. Equating their views to measurable outcomes identified two unique outcomes not really represented in the current literature from CORE8.1. These were ‘time to normal diet’ and ‘Appropriateness and accuracy of pre- operative information’. Conclusions: CORE8.1 has identified 82 outcomes across four domains, with a predominance of physical outcomes, particularly pain, swelling and mouth opening. CORE8.2 corroborated the importance of many of the CORE8.1 outcomes whilst adding new outcomes for consideration at future consensus stages to realise a COS for TMS (The CORE8). These were ‘time to normal diet’ and ‘Appropriateness and accuracy of pre-operative information’.
APPROVED
Keywords: outcome; core outcomes; third molar; oral surgery; wisdom tooth